Rainfall Data Modeling in Simalungun Regency Using the Arima Box-Jenkins Method - D, Desi Fransiska (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2024)
One of the components of the environment that determines the success of plant cultivation is climate. To predict rainfall, the author uses the ARIMA Box Jenkins method, which is a quantitative forecasting method. The data used are data for the period July 2012 to June 2017. In this study, the right model is the ARIMA model (2,0,2) with Xt = 4.05668 + 0.9416Xt-1 - 1.0039Xt-2 - 0, 8558et-1 + 0.9617et-2 + et which is used to forecast rainfall for the next 12 periods. The selection is based on the smallest MSE (average error squared) value of 0.033401954 and the smallest RMSE (root mean square error value), which is 0.001115691 and the smallest MAPE (absolute average error percentage) is -0 , 00801773.